2019
DOI: 10.28940/terra.v37i2.397
|View full text |Cite
|
Sign up to set email alerts
|

Efectividad de hongos micorrízicos arbusculares nativos de rizósfera de Agave como promotores de crecimiento de papaya

Abstract: Arbuscular mycorrhizal fungi (AMF) are benef icial symbionts of most terrestrial plants. This symbiosis brings benef its to both symbionts. The plant involved in the symbiosis is supplied with nutrients by the fungus that promotes plant growth, in exchange for energy for reproduction of the AMF. In this context, the effectiveness of multi-specif ic AMF inocula from the rhizosphere of Agave cupreata from Michoacán, Mexico, in promoting the growth of papaya plants was evaluated. An experiment was carried out in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…60,61,68,[76][77][78] There are numerous investigations that have the objective of evaluating the colonization and the effect of associated native mycorrhizal fungi on different plant species. 15,47,[79][80][81][82][83][84][85][86][87][88][89][90][91] Urgilés Gómez et al, 92 evaluated the effect of inoculation with native mycorrhizal fungi on the propagation of Alnus acuminata and Morella pubescens. The two species propagated in the greenhouse showed an improvement in growth when inoculated with propagules of mycorrhizal fungi, compared to the controls, and concluded that the symbiotic relationship between plant-fungus ensured their survival in the nursery and later in plantations for afforestation purposes, reforestation or restoration of ecosystems.…”
Section: Mycorrhizal Fungimentioning
confidence: 99%
“…60,61,68,[76][77][78] There are numerous investigations that have the objective of evaluating the colonization and the effect of associated native mycorrhizal fungi on different plant species. 15,47,[79][80][81][82][83][84][85][86][87][88][89][90][91] Urgilés Gómez et al, 92 evaluated the effect of inoculation with native mycorrhizal fungi on the propagation of Alnus acuminata and Morella pubescens. The two species propagated in the greenhouse showed an improvement in growth when inoculated with propagules of mycorrhizal fungi, compared to the controls, and concluded that the symbiotic relationship between plant-fungus ensured their survival in the nursery and later in plantations for afforestation purposes, reforestation or restoration of ecosystems.…”
Section: Mycorrhizal Fungimentioning
confidence: 99%
“…However, bacteria are not the only microorganisms that are able to promote plant growth. Mycorrhizal fungi also can carry out this function, there being a symbiotic association between them and most terrestrial plants [44] favoring micronutrient absorption, resistance to diseases caused by pathogens, or reduction of plant stress caused by environmental factors [45].…”
Section: Effects and Mechanisms Of Plant Growth Promotion By Microorgmentioning
confidence: 99%
“…Una alternativa para sustentar la producción de maíz en el estado de Chiapas es la inoculación con microorganismos promotores del crecimiento denominados biofertilizantes (Rivero-Herrada, 2016). Las bacterias de los géneros Rhizobium y Azospirillum, así como los hongos micorrízicos del género Glomus (Quiñones-Aguilar et al, 2012) son los más utilizados. Otra estrategia usada por los productores agrícolas es la incorporación de abonos verdes/cultivos de cobertura (AVCC), los cuales son considerados como una alternativa importante para conservar e incrementar la fertilidad de los suelos, debido a que permite sustituir la aplicación de fertilizantes químicos e incrementar la productividad de los cultivos.…”
Section: Introductionunclassified